UJI VIABILITAS SERBUK SARI Hemerocallis fulva L. (Liliaceae) SETELAH PENYIMPANAN PADA WAKTU DAN SUHU YANG BERBEDA - Sari Dewi Handayani, Ni Kadek; Kriswiyanti, Eniek; Astarini, Ida Ayu (Metamorfosa: Journal of Biological Sciences, 2013)
This study aims to determine the type of Hemerocallis fulva L. pollen, pollen viability and growth after storage at 280C, 40C, -200C, -800C temperature for 0-8 weeks. The study was conducted from January - March 2010. Pollen samples were taken from UPT. Botanical Gardens Plant Conservation 'Eka Karya’ Bali. Pollen storage and observations was carried out at the Laboratory of Plant Biotechnology and Development Structure, Biology Department, Faculty of Science, Udayana University. Viability test were conducted using hanging drop media and agar media with GA3. The results showed that type of Hemerocallis fulva L. pollen were: monosulkat, Prolate spheroiodal, (54.25 X 47.47), P/E: 1.14, Zono, colpate, reticulate. Fresh pollen viability on hanging drop media was 8.33%, decreased to 4% after storage at 4°C for one week and -20°C for 5 weeks. Whereas on agar media, control pollen has viability of 3.17% and increased at -20°C to become 11.67%. Mature pollen can be observed at the level of uninukleat, binukleat, and trinukleat. The development of pollen with the media hanging drop on the control has a long reed 115.94 ?m and length increased at 4 ° C with storage duration ie 256.39 weeks to 1 ?m, whereas on an agar medium + GA3 to control reed 149.82 ?m in length and at 28 ° C, 4 ° C, -20 ° C and -80 ° C respectively 94.73 ?m; 142.1 ?m; 95.53 ?m; 118.67 ?m at 1 week storage time.
Keywords: pollen viability, hanging drop, agar, GA3, pollen storage.